Моделирование параметров излучения между поверхностями произвольного положения с использованием точечного исчисления - Егорченков, Владимир Алексеевич (КНУБА, 2018)
При моделировании теплообмена излучением между поверхностями одним из основных параметров является угловой коэффициент облучённости. Его определение представляет особую сложность, и в настоящее время расчёты осуществляются для прямоугольных плоскостей, расположенных или параллельно или перпендикулярно друг другу. В реальности же поверхности могут занимать различные положения в пространстве и иметь многообразные формы. Поэтому целью данной работы является разработка метода моделирования параметров излучения между поверхностями, произвольно расположенными в пространстве и имеющими нестандартную форму с необходимой точностью на основе использования математического аппарата точечного исчисления. Для этого формируются множества точек сканирования. Для соседних четырёх точек сканирования определяются параметры излучения: тепловой поток, температура и коэффициент облученности и суммируются по всей площади поверхности. Разработанный метод моделирования позволит упростить эту задачу и сократить время расчётов, поскольку исключает составление громоздких систем уравнений, которые решаются численными методами. Дальнейшие исследования будут направлены на разработку программного комплекса по формированию комфортных температурно-влажностных условий в помещениях при наличии поверхностных излучателей различных форм и различно расположенных в пространстве. One of the components of thermal comfort for a person in a room is the amount of radiant heat perceived by him, which depends on the nature and amount of radiant heat exchange between the surfaces of the enclosing structures. The distribution of heat due to radiant heat transfer between the surfaces is similar to the light distribution and differs only in the wavelength. Therefore, the laws of propagation, reflection and refraction, established for visible light rays, are also valid for thermal radiation. This provision makes it possible to use the results of previous studies in determining the magnitude of the projection of the solid angle module in lighting calculations, which is identical to the irradiance coefficient. When simulating heat transfer by radiation between surfaces, one of the main parameters is the angular irradiance coefficient. Its definition is of particular complexity and at present calculations are carried out for rectangular planes located either parallel or perpendicular to each other. In reality, surfaces can occupy different positions in space and have multiple forms. Therefore, the aim of this work is to develop a method for modeling the radiation parameters between surfaces that are arbitrarily located in space and have a non-standard form, with the necessary accuracy based on the use of the mathematical apparatus of point calculus. For this, sets of scanning points are formed. For the adjacent four scan points, the radiation parameters are determined: heat flux, temperature, and irradiance coefficient and summed over the entire surface area. The developed method of modeling the parameters of radiant heat transfer over the surface of absorption of radiant heat from the surface of the radiator will simplify this task and reduce the computation time, since it eliminates the creation of cumbersome systems of equations that are solved by numerical methods. Further research will be focused on the development of a software package for the formation of comfortable temperature and humidity conditions in rooms with surface emitters of various shapes and variously located in space.
Simulation of Radiation Parameters Between Surfaces of Different Positions Using Point Calculation
https://doi.org/10.32347/2409-2606.2018.26.50-55
Keywords: моделирование; теплообмен излучением; угловой коэффициент облученности; точечное исчисление; температура; 628.87:004.925.8